Severe Intraperitoneal Haemorrhage following Suprapubic Catheter Insertion in a Patient Treated with Iloprost - R. A. J. Spence; A. Thwaini; Aidan O’Brien (Case Reports in Urology)
Suprapubic catheter (SPC) insertion is a common urological procedure, performed both in the elective and emergency settings. The authors present an unusual case of severe intraperitoneal bleeding following the insertion of an SPC under direct vision, where the use of prostacyclin analogue may have been a contributing factor.